Hippo Pathway and Skeletal Muscle Mass Regulation in Mammals: A Controversial Relationship - Gnimassou, Olouyomi; Francaux, Marc; Deldicque, Louise (Frontiers in Physiology, 2017)
Skeletal muscle mass reflects a dynamic turnover between net protein synthesis and degradation. In addition, satellite cell inclusion may contribute to increase muscle mass while fibre loss results in a reduction of muscle mass. Since 2010, a few studies looked at the involvement of the newly discovered Hippo pathway in the regulation of muscle mass. In line with its roles in other organs, it has been hypothesized that the Hippo pathway could play a role in different regulatory mechanisms in skeletal muscle as well, namely proliferation and renewal of satellite cells, differentiation, death and growth of myogenic cells. While the Hippo components have been identified in skeletal muscle, their role in muscle mass regulation has been less investigated and conflicting results have been reported. Indeed, the first studies described both atrophic and hypertrophic roles of the Hippo pathway and its effectors Yap/Taz using different biochemical approaches. Further investigation is therefore warranted to determine the role of the Hippo pathway in the regulation of skeletal muscle mass. New components of the pathway will probably emerge and unsuspected roles will likely be discovered due to its numerous interactions with different cellular processes. This mini-review aims to summarize the current literature concerning the roles of the Hippo pathway in the regulation of muscle mass and to develop the hypothesis that this pathway could contribute to muscle mass adaptation after exercise.